2014
DOI: 10.1074/jbc.m113.530212
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Streptococcus pneumoniae Endopeptidase O (PepO) to Complement Component C1q Modulates the Complement Attack and Promotes Host Cell Adherence

Abstract: Background: A detailed understanding of how pneumococci interact with the human host aids development of novel therapeutics. Results: PepO binds complement protein C1q and C4BP mediating pneumococcal-host cell adherence and evasion of the complement-mediated attack. Conclusion: PepO contributes to pneumococcal virulence. Significance: Pneumococci have multiple interrelated invasion and survival strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(96 citation statements)
references
References 35 publications
2
94
0
Order By: Relevance
“…Also, in vivo analysis using a mouse model revealed that S. pneumoniae PepO induces a strong innate immune response via the Toll-like receptor (TLR) 2 and TLR4 signaling pathways (26). Furthermore, secretory PepO of S. pneumoniae has an affinity to human C1q, thereby inhibiting C3b opsonization (16). On the other hand, surface-associated PepO contributes to bacterial adherence to host cells via its interaction with C1q.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Also, in vivo analysis using a mouse model revealed that S. pneumoniae PepO induces a strong innate immune response via the Toll-like receptor (TLR) 2 and TLR4 signaling pathways (26). Furthermore, secretory PepO of S. pneumoniae has an affinity to human C1q, thereby inhibiting C3b opsonization (16). On the other hand, surface-associated PepO contributes to bacterial adherence to host cells via its interaction with C1q.…”
Section: Discussionmentioning
confidence: 99%
“…pyogenes PepO Interacts with Human Complement Factor C1q-S. pneumoniae PepO has been shown to bind to human complement factor C1q, which leads to bacterial evasion from complement immunity via a classical pathway (16). Thus, we examined the direct interaction between S. pyogenes PepO and human C1q by SPR analysis at pH 7.4 ( Fig.…”
Section: S Pyogenes Endopeptidase Pepo Is Conserved and Expressed Inmentioning
confidence: 99%
See 3 more Smart Citations